2015
DOI: 10.15252/embj.201489642
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrin cytoskeleton regulates the Hippo signalling pathway

Abstract: The Spectrin cytoskeleton is known to be polarised in epithelial cells, yet its role remains poorly understood. Here, we show that the Spectrin cytoskeleton controls Hippo signalling. In the developing Drosophila wing and eye, loss of apical Spectrins (alpha/beta-heavy dimers) produces tissue overgrowth and mis-regulation of Hippo target genes, similar to loss of Crumbs (Crb) or the FERM-domain protein Expanded (Ex). Apical beta-heavy Spectrin binds to Ex and co-localises with it at the apical membrane to anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(177 citation statements)
references
References 75 publications
8
169
0
Order By: Relevance
“…Importantly, our model is easily reconciled with a possible role of YAP as a mechanosensor in epithelial tissues in vivo (Dupont et al, 2011). Mechanical force has been proposed to modulate signalling by both the apical Crb-Mer/Ex-Kibra-Sav system in Drosophila (Fletcher et al, 2015;Rauskolb et al, 2014) as well as the basal integrin-Src system in mammalian cell culture (reviewed in Humphrey et al, 2014;Lawson and Burridge, 2014). In the early mouse pre-implantation embryo, cortical tension is higher in outer cells than inner cells, leading to nuclear YAP in outer cells despite the presence of an apical domain (Anani et al, 2014;Kono et al, 2014;Nishioka et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Importantly, our model is easily reconciled with a possible role of YAP as a mechanosensor in epithelial tissues in vivo (Dupont et al, 2011). Mechanical force has been proposed to modulate signalling by both the apical Crb-Mer/Ex-Kibra-Sav system in Drosophila (Fletcher et al, 2015;Rauskolb et al, 2014) as well as the basal integrin-Src system in mammalian cell culture (reviewed in Humphrey et al, 2014;Lawson and Burridge, 2014). In the early mouse pre-implantation embryo, cortical tension is higher in outer cells than inner cells, leading to nuclear YAP in outer cells despite the presence of an apical domain (Anani et al, 2014;Kono et al, 2014;Nishioka et al, 2009).…”
Section: Discussionmentioning
confidence: 58%
“…By contrast, columnar epithelia differentiate an apical domain that induces YAP relocalisation to the cytoplasm via apical CRB3-MER-KIBRA-SAV signals, which are known to activate the MST and LATS kinases to promote YAP phosphorylation and cytoplasmic retention despite contact with the basement membrane (Figs 6,7, (Baumgartner et al, 2010;Chen et al, 2010;Fletcher et al, 2015;Genevet et al, 2010;Hamaratoglu et al, 2006;Ling et al, 2010;Sun et al, 2015;Szymaniak et al, 2015;Varelas et al, 2010;Yin et al, 2013;Yu et al, 2010). The CRB3-MER-KIBRA-SAV complex appears to be absent in squamous epithelia, which never differentiate a true apical domain, leaving basement membrane contact as the sole regulatory mechanism (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This subject has been comprehensively reviewed elsewhere (Schroeder and Halder 2012;. Recent studies show that loss of Spectrin, a contractile protein at the cytoskeleton-membrane interface, also generates Hpo mutant-like tissue overgrowth phenotypes in Drosophila wings and eyes, which are likely due to dysregulated cytoskeleton tension Fletcher et al 2015;Wong et al 2015).…”
Section: Cell Polarity and Architecturementioning
confidence: 99%
“…In Drosophila or non-hepatic mammalian cells, multiple upstream inputs including extracellular matrix area and stiffness [72,73], cell density [54], cell detachment [74], Factin cytoskeleton [75], spectrin cytoskeleton [76,77], and cellular energy level [78,79] were shown to regulate YAP nuclear accumulation dependent or independent of the canonical Hippo signaling. Detailed reviews of these upstream YAP regulators can be found elsewhere [80,81].…”
Section: Yap Mrna Transcriptionmentioning
confidence: 99%